Medieval merchants and money : essays in honour of James L. Bolton - Allen, Martin, 1956-; Davies, Matthew P.; Bolton, J. L. (Institute of Historical Research, 2016)
"This volume contains selected essays from a conference held in November 2013 to celebrate the contribution to scholarship of the medieval historian Professor James L. Bolton. Within the overall theme, the essays address a number of different questions in medieval economic and social history, focussing in particular on the activities of merchants, their trade, legal interactions and identities, and on the importance of money and credit in the rural and urban economies. Other essays look more widely at patterns of immigration to London, trade and royal policy, and the role that merchants played in the Hundred Years War."--Back cover.